Paracoccidioidomycosis, cutaneous Leishmaniasis, Sporotrichosis, Chromomycosis, Cutaneous Tuberculosis or Nontuberculous Mycobacteria? - João Victor Soares Coriolano Coutinho; Taiguara Fraga Guimarães; Renata de Bastos Ascenço Soares (Clinical Infection in Practice)
This manuscript presents a rare case of cutaneous tuberculosis, characterized by an extensive array of skin lesions that could easily be mistaken for other infectious diseases, necessitating a thorough investigation.